Relative incidences and outcomes of Clostridium difficile infection following transplantation of unrelated cord blood, unrelated bone marrow, and related peripheral blood in adult patients: a single institute study. Issue 3 (9th May 2014) - Hosokawa, K.; Takami, A.; Tsuji, M.; Araoka, H.; Ishiwata, K.; Takagi, S.; Yamamoto, H.; Asano‐Mori, Y.; Matsuno, N.; Uchida, N.; Masuoka, K.; Wake, A.; et al.
Abstract Background Clostridium difficile is a major cause of nosocomial diarrhea. The incidence and prognosis of C. difficile‐associated diarrhea (CDAD) has not yet been assessed in adult patients after unrelated cord blood transplantation (uCBT). Methods The medical records of 135 adult unrelated cord blood transplant recipients were reviewed retrospectively to investigate the clinical features of CDAD after uCBT. These data were compared to medical records of 39 unrelated bone marrow transplant recipients and 27 related peripheral blood stem cell transplant recipients as controls. Results A total of 17 recipients developed CDAD, with onset occurring at a median of 22 days (range, 0–56 days) after transplantation. Among the unrelated cord blood transplant recipients, 11 (9%) developed CDAD. These results were comparable with those of CDAD after unrelated bone marrow transplantation (uBMT) (2/39, 6%) and related peripheral blood stem cell transplantation (rPBSCT) (4/27, 16%) (P = 0.37). Fifteen of the infected recipients were successfully treated with oral metronidazole, vancomycin, or cessation of antibiotics. The remaining 2 recipients who developed CDAD after uCBT died of other causes. The development of CDAD did not negatively affect overall survival after uCBT. Conclusions These data indicate that the incidence and prognosis of CDAD after uCBT are comparable with those after uBMT and rPBSCT.